Analisis Determinan Pertumbuhan Ekonomi Regional dengan Menggunakan Model Panel Data - Muh. Nur; Rince Tambunan; Kusman Paluala (Journal of Economics, Management, and Accounting, 2025)
Regional economic growth is one of the main indicators for measuring development progress at the regional level. In Indonesia, which consists of various provinces with diverse economic characteristics, understanding the factors that determine this growth is crucial for formulating appropriate policies. This study aims to analyze the determinants of regional economic growth using a panel data model, focusing on variables such as investment, labor, education, and infrastructure. The data used comes from 34 provinces in Indonesia during the 2019-2024 period, which was analyzed using a panel regression approach with a fixed effect model. The results show that infrastructure has a positive and significant effect on economic growth, while the variables of investment, labor, and education show no statistically significant effect. These findings imply that local governments need to prioritize infrastructure development to promote sustainable growth. In addition, this study also discusses policy implications in the context of regional inequality in Indonesia. Overall, this analysis contributes to the regional economics literature by emphasizing the importance of panel data in capturing inter-regional and inter-temporal variation.